Pelaksanaan Peraturan Menteri BUMN Nomor: PER-01/MBU/2011 Tentang Penerapan Tata Kelola Yang Baik (Good Corporate Governance) Pada BUMN (Studi Kasus Di PT Perkebunan Nusantara IV) - Hartono, Rudi; Marlina, Marlina; Muaz Zul, Muaz Zul (ARBITER: Jurnal Ilmiah Magister Hukum, 2020)
Good Corporate Governance can be understood as a set of regulations governing Limited Liability relationship between shareholders, management companies and other stakeholders with regard to the rights and obligations, one of which is the decision-making at the Board of Directors and Board of Commissioners. The provisions stipulated in the Regulation of the Minister of SOE No. PER-01 / MBU / 2011,  the publication of these regulations ultimately aims to create corporate  governance that provides added value for all parties. The research method used is a normative legal research methods that are qualitative, such methods researchers conducted a discussion of the law in legislation through legal theories that found the answers to legal issues in accordance with applicable regulations. Barriers to implementation of  Good Corporate Governance is composed of several factors, among others, legal, corporate culture and human resources, but the implementation of PT Perkebunan Nusantara IV remain committed. As part of its commitment to the forming section, which is responsible for monitoring and encouraging implementation of application in accordance with the provisions of the Law.